2021
DOI: 10.1051/0004-6361/202141531
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical computations on the efficiency of acetaldehyde formation on interstellar icy grains

Abstract: Context. Interstellar grains are known to be important actors in the formation of interstellar molecules such as H2, water, ammonia, and methanol. It has been suggested that the so-called interstellar complex organic molecules (iCOMs) are also formed on the interstellar grain icy surfaces by the combination of radicals via reactions assumed to have an efficiency equal to unity. Aims. In this work, we aim to investigate the robustness or weakness of this assumption. In particular, we consider the case of acetal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 84 publications
2
15
0
Order By: Relevance
“…For instance, in acetaldehyde formation by the coupling of CH 3 and HCO, the coupling temperature window was found to be between the temperatures at which CH 3 becomes mobile on the surface (between 9 and 15 K, depending on the adopted diffusion barrier) and the temperature at which the methyl radical would desorb (30 K). 55 Another drawback is that radical–radical couplings are often assumed to be barrierless because they are driven by the coupling of the opposite electronic spins of the radicals. However, the reactions can exhibit energy barriers because the radicals, to proceed with the coupling, need to break the interactions with the icy surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in acetaldehyde formation by the coupling of CH 3 and HCO, the coupling temperature window was found to be between the temperatures at which CH 3 becomes mobile on the surface (between 9 and 15 K, depending on the adopted diffusion barrier) and the temperature at which the methyl radical would desorb (30 K). 55 Another drawback is that radical–radical couplings are often assumed to be barrierless because they are driven by the coupling of the opposite electronic spins of the radicals. However, the reactions can exhibit energy barriers because the radicals, to proceed with the coupling, need to break the interactions with the icy surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Besides its ubiquity and comparatively high gas phase abundance mentioned in the introduction, it has been tentatively suggested as a possible carrier of the weak 7.41 µ m band recorded in observations of the Infrared Space Observatory (ISO-SW) towards the young stellar object W 33A (Schutte et al 1999). As demonstrated by theoretical studies, acetaldehyde can be formed from the recombination of CH 3 and CHO on dust grains (Lamberts et al 2019;Enrique-Romero et al 2021). Such recombination is a highly exothermic process that, in combination with the relatively low binding energy of the molecule with ASW, may suggest a return to the gas phase of the nascent molecule via non-thermal effects.…”
Section: Discussionmentioning
confidence: 97%
“…To this aim, theoretical calculations and experiments can provide helpful information. For example, concerning acetaldehyde, two theoretical works were recently published that investigate the formation of CH 3 CHO on CO or water-ice surfaces (Lamberts et al 2019;Enrique-Romero et al 2021). These latter studies found a route for CH 3 HO formation on dust grains via recombination of CH 3 and CHO radicals.…”
Section: Introductionmentioning
confidence: 99%
“…3,[51][52][53] And, additionally, they have also been assumed to study the formation of iCOMs by means of quantum chemical simulations. [54][55][56][57] By compiling all the available works, it seems that both paradigms are necessary to explain the presence, distribution and abundance of the wide and rich organic chemistry in the ISM. Thus, knowing whether the formation of an iCOM is dominated by surface or gas-phase chemistry is a case-by-case problem.…”
Section: Introductionmentioning
confidence: 99%